Analisis Pengaruh Pola Asuh Terhadap Kecelakaan Lalu Lintas pada Pelajar SMA Menggunakan Regresi Logistik - Febrianti Qisti Arrum Bayumi; Lucia Yovita Hendrati (Jurnal Biometrika dan Kependudukan (Journal of Biometrics and Population), 2019)
Injuries due to traffic accidents were ranked eighth as health problem that caused deaths in several countries. Many traffic accidents occur in Africa and Southeast Asia with mortality rate of 26.6 and 20.7 deaths per 100,000 populations in 2016. East Java Province was ranked second as the location of traffic accidents on Java. Surabaya was ranked fifth as a contributor to the large number of road traffic accidents in East Java. The purpose of this study is to identify the relationship between parents’ authoritarian parenting and the experience of teenage traffic accidents while riding a motorcycle. This research is a cross sectional study and uses two stage random sampling method. From the sampling process, as many as 222 students were obtained as respondents. The instrument used in this study consists of personal data and the Parental Authority Questionnaire (PAQ) to identify parenting style. Data analysis was carried out by logistic regression test with α= 5%. The data collection process was carried out during April-October 2017 in public and private high school in Surabaya. Logistic regression test results showed that there is no significant impact between parenting style and traffic accidents experienced by respondents (authoritarian p = 0.966; OR = 0.967, permissive p = 0.616; OR = 1.556). The conclusion of this study is that traffic accidents are not directly affected by parenting style, but it has role in forming individual characteristics, such as decision making and driving attitudes.